DETECTION OF TUMOR NECROSIS FACTOR- (TNF- ) GENE PROMOTERS POLYMORPHISM AMONG LIVER CIRRHOSIS PATIENTS WITH CHRONIC HEPATITIS B VIRUS (HBV) INFECTION IN SURABAYA, INDONESIA - Wungu, Citrawati Dyah Kencono; Amin, Mochamad; Ruslan, S. Eriaty N.; Purwono, Priyo Budi; Kholili, Ulfa; Maimunah, Ummi; Setiawan, Poernomo Boedi; Lusida, Maria Inge; Soetjipto, Soetjipto; Handajani, Retno (Indonesian Journal of Tropical and Infectious Disease, 2019)
Polymorphisms in TNF-α gene promoter region are known of its role in the production of TNF-α which may influences the pathogenesis of liver disease. SNPs in positions 238 and 308 of TNF-α gene promoters may affect the production of these cytokines. This study was aimed to detect Single Nucleotide Polymorphism (SNP) on -238 and -308 positions in the TNF-α gene promoter among liver cirrhosis patients with HBV infection in Surabaya, Indonesia. This was descriptive exploratory research with cross sectional study design using serum liver cirrhosis patients with HBV infection in Endoscopy Outpatient Clinic Dr. Soetomo General Hospital, Surabaya from April-May 2017. SNPs at -238 and -308 on TNF-α gene promoter (rs361525 and rs1800629 respectively) were detected using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) with primers specific for the TNF-α promoter region and restriction enzymes NcoI and MspI. The genotypes of TNF-α gene promoter were assessed according to the length of the fragments produced in RFLP. Serum TNF-α levels was measured by commercial ELISA. In this study, as much as 149 positive HBsAg patients was found in Endoscopy Outpatient Clinic, Dr. Soetomo General Hospital, Surabaya. From those amount, as much as 30 liver cirrhosis patients with positive HBsAg were obtained. From 2/30 (6.7%) patients showed the GA heterozygote SNP either position -238 or -308. No patient had the AA genotype. Median blood TNF-α level in women (38 ng / L) was higher than in men (33 ng / L). TNF-α levels in patients with GA heterozygote genotype at -238 and -308 in this research was not different than wild-type (GG genotype). Among patients with liver cirrhosis due to chronic HBV infection in Surabaya, Indonesia, Surabaya, we found GA polymorphisms the TNF-α promoter gene at positions -238 and -308 in 6.7% patients, and did not find homozygous AA polymorphisms. Further studies including larger numbers of patients from various ethnic backgrounds in Indonesia are needed to provide robust data on TNF-α gene promoter polymorphisms and their role in the pathogenesis of liver cirrhosis with HBV infection in this country.